å¤ç”¸åˆä¸å¦æ ¡ä½¿ç”¨æ±‰è¯æ•™ææƒ…å†µåˆ†æž - Rohaini, Eka; Ina, Ina; Lusi, Lusi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Three factors of Chinese language teaching are teacher, student, and teaching materials. Teaching materials are a crucial part of Chinese part of language learning. Some Chinese books published by Chinese publisher, some from indonesia, and others are written by teachers. For a deeper understanding of the utilization of Chinese Teaching Materials at Junior High School at Pontianak, the author conducted interviews with 13 schools. Then, combined with the specific use of Chinese Teaching Materials in Pontianak Junior High Schools, a statistical analisys divided into three points: 1. Analysis of the use of teaching materials from China, 2. Analysis of the use of teaching materials from Indonesia, 3. Analysis of teaching materials written by teachers. The results showed that the Teaching Materials from China used in Pontianak Junior High School were "Hanyu", "Zhongwen" dan "HSK", Teaching Materials from Indonesian are "Zhineng Hanyu", "Chunhui", dan "You Zhongwen Goutong", and Teaching Materials written by teacher "Gen Wo Xuexi Hanyu" Modul Bahasa Tionghoa" and "Hanyu Keben". These proved that most Pontianak Junior High Schools use Chinese Teaching Materials, and most Pontianak Junior High Schools the similiar teaching materials namely "Hanyu". The reasons why the teachers chose "Hanyu" are all the same. All teachers indicated that this set of teaching Materials is easier for stuents to understand. The advantage of "Hanyu" is the vocabularies, because those vocabularies often used in daily life. All teachers indicated that "Hanyu" teaching materials can improve students Chinese proficiency